2020
DOI: 10.3389/fphar.2020.00452
|View full text |Cite
|
Sign up to set email alerts
|

Gerontoxanthone I and Macluraxanthone Induce Mitophagy and Attenuate Ischemia/Reperfusion Injury

Abstract: Mitophagy is a crucial process in controlling mitochondrial biogenesis. Balancing mitophagy and mitochondrial functions is required for maintaining cellular homeostasis. In this study, we found that Gerontoxanthone I (GeX1) and Macluraxanthone (McX), xanthone derivatives isolated from Garcinia bracteata C. Y. Wu ex Y. H. Li, induced Parkin puncta accumulation and promoted mitophagy. GeX1 and McX treatment induced the degradation of mitophagy-related proteins such as Tom20 and Tim23. GeX1 and McX directly stabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…Gerontoxanthone I (GeX1) and macluraxanthone (McX), which have been proposed to elicit protective effects against myocardial IR injury, have been shown to promote PINK1 stabilization and Parkin phosphorylation and induce the degradation of mitophagy-related proteins, such as TOMM20 and TIMM23, inducing mitophagy through the PINK1-Parkin pathway [ 428 ].…”
Section: Targeting Mitophagymentioning
confidence: 99%
“…Gerontoxanthone I (GeX1) and macluraxanthone (McX), which have been proposed to elicit protective effects against myocardial IR injury, have been shown to promote PINK1 stabilization and Parkin phosphorylation and induce the degradation of mitophagy-related proteins, such as TOMM20 and TIMM23, inducing mitophagy through the PINK1-Parkin pathway [ 428 ].…”
Section: Targeting Mitophagymentioning
confidence: 99%
“…30 Macluraxanthone (1) has also been isolated from different species of the Clusiaceae, e.g. Garcinia opaca, 24 G. ovalifolia, 31 G. speciose, 32 G. bracteata 33 and Rheedia gardneriana 34 and Calophyllaceae, e.g. Calophyllum soulattri, 35 C. inophyllum, 36,37 C. caledonicum, 38 C. blancoi 25 and Mesua ferrea, 39 and has been reported as having antioxidant, antimalarial, cytotoxic, and antiischemic activities.…”
Section: Resultsmentioning
confidence: 99%
“…Calophyllum soulattri, 35 C. inophyllum, 36,37 C. caledonicum, 38 C. blancoi 25 and Mesua ferrea, 39 and has been reported as having antioxidant, antimalarial, cytotoxic, and antiischemic activities. 32,33,[39][40][41][42][43] It is important to mention that, even though most of the experimental chemical shifts values for the various protons and carbons of 1 coincided with those reported for macluroxanthone (1) (Table 1), 24,25 the HMBC experiment allowed the correct assignment of the C-8a and C-9a carbon signals, on the basis of the observed correlations between the proton of the hydroxyl group at C8 and the C-8a carbon, and between the H-2 proton and the C-9a carbon (Figure S7, Supporting Information Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, deletion of PINK1 in this context abrogates the beneficial effect of hydrogen, suggesting that over-activation of PINK1/parkin-mediated mitophagy is essential for the anti-apoptotic and anti-inflammatory effect of hydrogen during cardiac I/R [ 95 ]. Furthermore, several studies showed that pharmacological activation of PINK1/parkin-mediated mitophagy is cardioprotective following H/R [ 103 , 104 , 105 ].…”
Section: Role Of Mitophagy During and Following Myocardial Infarction (Mi)mentioning
confidence: 99%